수학,과학 학업성취도 결정요인 종단연구 - 이현철; Hyun Chul Lee (과학교육연구지, 2010)
본 연구에서는 한국청소년패널조사(Korea Youth Panel Survey) 1차년도(2003년)-4차년(2006년)도의 방대한 종단적 자료를 활용하여 학업성취 영향을 주는 다양한 변인들을 투입하여 한국청소년들의 수학·과학 학업성취도의 종단적 변화의 패턴을 탐색하고, 수학·과학 학업성취도 초기 형성과 변화에 영향을 주는 요인들을 분석하고자 한다. 이를 통해 영재성 판별의 주요한 측면을 담당하고 있는 수학·과학 학업성취도의 개선을 위한 기초자료를 제공하고자 하였다. 연구결과를 통해 수학·과학 학업성취도 변화 패턴은 이차곡선적인 패턴을 보여주고 있었으며, 수학은 감소하는 성장모형을, 과학은 증가하는 성장모형으로 확인되었다. 또한 수학·과학 학업성취에 영향을 주는 요인을 분석함으로써 수학·과학 학업성취 초기치와 변화율 그리고 이차곡선요인에 부모관계, 교사관계, 자아관, 월평균소득, 진학계열이 주요하게 영향력 주고 있다. 그러나 아버지 직업의 경우 통계적으로 무의미하였다. 이를 통해 영재성 판별의 주요한 측면을 담당하고 있는 수학·과학 학업성취도의 개선을 위해서는 부모관계, 교사관계의 건강한 개선과 학생들의 올바른 자아관 확립 그리고 소외계층을 향한 우리 사회의 다양한 정책 및 학교 내 프로그램들이 다양한 수준에서 개발될 필요가 있음을 시사하고 있다. This study analyzes the factors influencing academic achievement on mathematic and scientific subject and its change in Korean youth by using a sample from KYPS(Korea Youth Panel Survey) data. The results are as follows: First, academic achievement on mathematic and scientific subject of Korean youth shows quadratic curve that their interrelationship between intercept and slope of academic achievement are negative which is statistically significant. Second, analysis of Latent Growth Models shows that parents, teacher, peer group, self esteem, income of family, high school tracks are found to be a statistically significant factor on mathematic. And scientific subject is affected by parents, teacher, peer group, self esteem, income of family, high school tracks. Also, Interesting finding is that father`s job is not significant to dependent variables. These findings show that academic achievement on mathematic and scientific subject of the Korean youth are the quadratic curve and influenced by parents, teacher, peer group, self esteem, income of family, high school tracks. To improve youth`s mathematic and scientific, Korea educational fields and educators should have policy to care youth`s relationship with parents, teachers and self esteem.